Persepsi Masyarakat Terhadap Keberadaan Rumah Potong Hewan di Kelurahan Tahoa, Kolaka, Sulawesi Tenggara (COMMUNITY PERCEPTION ON EXISTENCE OF ABATTOIR IN TAHOA VILLAGE, KOLAKA DISTRICT, SOUTH EAST SULAWESI PROVINCE, INDONESIA) - Suparman, Suparman; Arif, Muhammad (Jurnal Veteriner, 2020)
Meat is one of the livestock products producing from abattoir, which in its implementation must be able to maintain good quality including of cleanliness, health, and halal for consuming by coommunity. This study aims to determine the community’s perception on the existence of abattoirs in the Tahoa Village, Kolaka District. This research is quantitative descriptive using a Likert scale. The samples used in this study ware 34 people. The results of the study showed that of the odor variable has a value of 357 and categorized as in the disturbed category. As well as for, water pollution with a value of 207 was categorized as quite disturbed and also for waste with a value of 233 was categorized as quite disturbed. The total of all three sub-variable values   (odor, water pollution and waste) was 797, and it was categorized as moderately disturbed. In conclusion of this study shows that the community’s perception of the existence of abattoirs in the Tahoa Village, Kolaka District, is quite disturbed.